2016
DOI: 10.1038/srep23864
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy Negatively Regulates Transmissible Gastroenteritis Virus Replication

Abstract: Autophagy is an evolutionarily ancient pathway that has been shown to be important in the innate immune defense against several viruses. However, little is known about the regulatory role of autophagy in transmissible gastroenteritis virus (TGEV) replication. In this study, we found that TGEV infection increased the number of autophagosome-like double- and single-membrane vesicles in the cytoplasm of host cells, a phenomenon that is known to be related to autophagy. In addition, virus replication was required … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
72
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(73 citation statements)
references
References 67 publications
1
72
0
Order By: Relevance
“…Since viral translation for replication occurs in the cytoplasm of target cells (Lee, 2015), we postulated that autophagy which removes unnecessary cytoplasmic components (Levine et al, 2011;Reggiori and Klionsky, 2002) might be a potential effective defense mechanism against PEDV. With reference to existing results showing that autophagy can restrict invasion of other viruses including Transmissible gastroenteritis coronavirus (Guo et al, 2016), HSV-1 (Yakoub and Shukla, 2015), and Rift Valley fever virus (Moy et al, 2014), we demonstrated that rapamycin treatment in porcine IECs has a protective function against PEDV through the uptake of the virus into autophagosomes at an early stage of infection. To the best of our knowledge, this study is the first to describe the defensive mechanism of autophagy against PEDV infection in porcine IECs.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…Since viral translation for replication occurs in the cytoplasm of target cells (Lee, 2015), we postulated that autophagy which removes unnecessary cytoplasmic components (Levine et al, 2011;Reggiori and Klionsky, 2002) might be a potential effective defense mechanism against PEDV. With reference to existing results showing that autophagy can restrict invasion of other viruses including Transmissible gastroenteritis coronavirus (Guo et al, 2016), HSV-1 (Yakoub and Shukla, 2015), and Rift Valley fever virus (Moy et al, 2014), we demonstrated that rapamycin treatment in porcine IECs has a protective function against PEDV through the uptake of the virus into autophagosomes at an early stage of infection. To the best of our knowledge, this study is the first to describe the defensive mechanism of autophagy against PEDV infection in porcine IECs.…”
Section: Discussionmentioning
confidence: 52%
“…In general, most studies on in vitro viral infection use infection times of 60 min (Guo et al, 2016;Shelly et al, 2009;Zhao et al, 2014). For example, Zhao et al showed a slight change in tight junction protein expression and permeability of porcine IECs, followed by a rapid recovery after 1 h of PEDV or TEGV infection (Zhao et al, 2014).…”
Section: Rapamycin Has a Protective Effect On Cell Death Induced By Lmentioning
confidence: 99%
See 1 more Smart Citation
“…LC3-specific siRNAs (small interference RNA) (5′-GAGUGAGCUCAUCAAGAUAtt-3′) and an unrelated control siRNA (5′-UUCUCCGAACGUGUCACGUtt-3′) [30] were synthesized from GenePharma Co., Ltd., to knockdown of LC3 expression. HCT116 cells were transfected with 100 nM LC3 siRNA or nonrelated control siRNA.…”
Section: Methodsmentioning
confidence: 99%
“…Transmissible gastroenteritis virus (TGEV) 1 , an enteropathogenic coronavirus, is an enveloped virus with a positivesense single-stranded RNA genome (1). TGEV infection can cause apoptosis, inflammation, immune response, autophagy (2)(3)(4). We reported that TGEV infection could induce cell apoptosis via mitochondria-mediated pathway and caused a decrease of mitochondrial membrane potential, implying that mitochondrial dysfunction occurs (5,6).…”
mentioning
confidence: 99%